Uncommon presentation of lichen planopilaris during paclitaxel chemotherapy: Case report - Nwanneka M Okwundu; Felicia E Ekpo; Jessica Ghafferi; David Fivenson (Wolters Kluwer Medknow Publications, 2020)
Lichen planopilaris (LPP) is an uncommon scalp disorder of unknown etiology and prevalence. It may be an autoimmune process triggered by unknown genetic and/or environmental factors that attack hair follicles of the scalp. LPP can present in association with various autoimmune diseases and immunomodulatory therapies. We present an atypical case of LPP occurring during the treatment of breast cancer with paclitaxel, after complete resolution of alopecia areata and anagen effluvium. Shortly after initiation of the paclitaxel therapy, the patient experienced a pruritic acneiform facial eruption and hair loss that was localized to her frontal scalp with complete loss of eyebrows and significant loss of her eyelashes. The lesions were biopsied revealing LPP. LPP should be considered among other causes of alopecia in patients treated with paclitaxel.